Educação ambiental em municípios petrolíferos de Sergipe : realidades e possibilidades - Silva, Phellipe Cunha da (2014)
This study was prepared from the concern about how effective the environmental education in the oil towns of Sergipe is. To do this analysis we seek references in two municipalities of oil in the conditions offered for the comparison of the possibilities of bringing environmental education. The chosen cities were Carmópolis and Pirambu. Carmópolis is a town where oil exploration occurs in onshore mode and at Pirambu, the oil exploration occurs predominantly offshore. These differences are representative because of the type of operation is directly related to how the environment is impacted and also how this impact is perceived by the inhabitants. This work aimed to analyze the effectiveness of formal and non-formal environmental education in the towns of Carmópolis and Pirambu, with a view to propose a joint effort between the government and oil exploration companies. Therefore, we list the following objectives: to analyze the historical development of environmental issues; to relate the environmental education and its insertion into the formal and non-formal education; to present the economic potential of municipalities from oil royalties and the possibilities of interconnections between them and the environmental education. From the literature review and interviews it became clear that environmental education in both cities can be carried out efficiently, if there is involvement of all sectors of society.